A clinical review on importance of sanitizing the operating room - Singh, Mahendra; Alam, Mohammad (International Journal of Research in Medical Sciences, 2024)
Modern day surgery is a highly sophisticated procedure incorporating both invasive and non-invasive techniques that are performed in the operation theatres. But we cannot ignore the fact that the infections are often acquired in hospital are surgical sites. The infection may transfer from patient to staff, staff to patients or patient to patient. Hence the aim of infection control practice is reducing the risk of infection from the surgical site. These practices include surgical scrubbing, disinfection of operating rooms, equipment and sterilization of instruments. Hand washing is done before and after dealing the patients, before surgical procedure with anti-septic solution or alcohol based sanitizer. The sanitizing techniques play an important role in avoiding infections and their spread in operating room. The knowledge of various techniques of disinfection and sterilization are more essential for staff members. These include but not limited to preparation of disinfectants and their concentration. For surgical instruments we use steam sterilizer (auto-clave) and ethylene oxide for endoscopic instruments. There is a need of training the surgical staff members to carry out these practices.